Optimization of Essential Oil Production from Clove Leaves and Clove Handles (Syzgium Aromaticum) Using UAP Distillation Method: Optimasi Produksi Minyak Atsiri dari Daun Cengkeh dan Gagang Cengkeh (Syzgium Aromaticum) Menggunakan Metode Destilasi UAP - Sugiharto, Agung; Kinanda, Amalia; Nugroho, Aris Tri (Prosiding University Research Colloquium, 2023)
Clove oil is one of the essential oils from the clove tree (syzygium aromaticum) which is abundant in Indonesia. Essential oil can be made from the leaves and handles of deciduous cloves. The composition of the oil produced varies depending on the state of the leaves and the method of distillation. The quality of essential oil is largely determined by the properties and chemical compounds contained therein. This study uses the steam distillation method to extract oil from clove leaves and clove handles. Clove leaves are dried according to variations in drying time. The variation of drying time used is 1 day, 3 days, 7 days, and 14 days. Clove leaves were chopped until slightly fine and then weighed as much as 2000 grams. While the study distilled 2000 grams of clove handle into a distillation kettle with a variety of feeds, namely 2 mesh and 8 mesh. This study aims to determine the optimization of the length of leaf drying time used, the effect of distillation process time, and the most optimal yield that can be produced, density analysis and refractive index analysis. The results of this study are expected to provide more knowledge related to clove leaf oil production.